Compound Optimal Designs for Percentile Estimation in Dose-Response Models with Restricted Design Intervals - Holger Dette; Stefanie Biedermann; Wei Zhu (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
In dose-response studies, the dose range is often restricted due to ethics concerns over drug toxicity and/or efficacy, particularly when human subjects are involved. We present locally optimal designs for the estimation of several percentiles simultaneously on restricted as well as unrestricted design intervals. Our results are applicable to most of the commonly applied link functions with respect to the model under consideration. This work is a generalization of Dai (2000) where he showed that the same results hold for the logit model using Elfving?s approach on trace optimal design (Elfving, 1952).
Keywords: 519; Dose-response model; link function; percentile estimation; compound optimal design; A-optimality